'Determined to breastfeed': A case study of exclusive breastfeeding using interpretative phenomenological analysis. Issue 4 (August 2017) - Charlick, Samantha J.; Fielder, Andrea; Pincombe, Jan; McKellar, Lois
Abstract: Background: Given the significant benefits of breastfeeding, the World Health Organization (WHO) recommend exclusive breastfeeding for six months. Despite numerous strategies aimed at increasing the percentage of babies who are exclusively breastfed, Australia currently has one of the lowest six-month exclusive breastfeeding rates in the developed world. Notably, most research focuses on the early postnatal period (birth-two months) yet the largest decline in exclusive breastfeeding rates is observed between two and six months. Aim: This study aimed to understand what enabled a first-time mother to continue exclusively breastfeeding between two and six months in Australia. Methods: The qualitative approach known as interpretative phenomenological analysis (IPA) was used to explore how the new mother understood her exclusive breastfeeding journey. Data was collected retrospectively through a face-to-face, semi-structured interview, then transcribed in full and analyzed using IPA's approach to data analysis. Findings: Three main themes were identified as self-determination to achieve exclusive breastfeeding, the influence of social norms in Australian culture, and the impact social supports have on maintaining exclusive breastfeeding. Conclusion: For this mother, her self-determination to exclusively breastfeed, along with positive social support, outweighed the impact of perceived social norms and negative pressure from significant others to stop exclusive breastfeeding. This qualitative reflection contributes to an understanding of the individual in the breastfeeding journey, uncovering nuances around exclusive breastfeeding that may be helpful in providing support for mothers and direction for further research.